Sistema infromático para el registro y control académico mediante sincronización web móvil para la Institución Educativa Barrio Obrero de la ciudad de Ipiales - Villarreal Reina, Diana Carolina (2015)
This paper deals with the research and development of a computerized system for recording and academic control synchronization via mobile web (WAP) for Educational Institution Barrio Obrero City Ipiales, allowing that institution to be technologically updated in a way innovative and above all useful. Has seen fit to develop this research because the educational institution Barrio Obrero has an cutdated academic system and various faults which does not allow you the right academic performance and does not meet the needs of the institution. The line of research that has been considered for this research is system programming and software development, the methodology applied specifically is the object-oriented methodology with its different stages, plus it relies on methods of empirical research and theoretical. This research concludes with the implementation of a new computer system that serves as a great support decision-making and with latest technology in mobile web synchronization.